2016
DOI: 10.1016/j.jsbmb.2015.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of sex specific endocrine disrupting effects in the prenatal and pre-pubertal rodent brain

Abstract: Background Brain sex differences are found in nearly every region of the brain and fundamental to sexually dimorphic behaviors as well as disorders of the brain and behavior. These differences are organized during gestation and early adolescence and detectable prior to puberty. Endocrine disrupting compounds (EDCs) interfere with hormone action and are thus prenatal exposure is hypothesized to disrupt the formation of sex differences, and contribute to the increased prevalence of pediatric neuropsychiatric dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(57 citation statements)
references
References 124 publications
(150 reference statements)
5
48
0
4
Order By: Relevance
“…Thus BPA exposure during development is able to disrupt sexually dimorphic behaviors in different species by disrupting normal steroid programming of the brain. Numerous studies have confirmed the ability of BPA and other EDs to affect the developing brain in a sex specific way even at very low doses (Patisaul and Polston, 2008;Martini et al, 2010;Cao et al, 2013;Rebuli and Patisaul, 2016). Altogether these findings suggest that when considering any developmental factor, an hypothesis it is not that males and females are more susceptible to a given developmental factor, but rather that developmental factors have sexually dimorphic consequences that need to be accounted for.…”
Section: Sex-dependent Effects Of Developmental Events: the Case Of Ementioning
confidence: 81%
“…Thus BPA exposure during development is able to disrupt sexually dimorphic behaviors in different species by disrupting normal steroid programming of the brain. Numerous studies have confirmed the ability of BPA and other EDs to affect the developing brain in a sex specific way even at very low doses (Patisaul and Polston, 2008;Martini et al, 2010;Cao et al, 2013;Rebuli and Patisaul, 2016). Altogether these findings suggest that when considering any developmental factor, an hypothesis it is not that males and females are more susceptible to a given developmental factor, but rather that developmental factors have sexually dimorphic consequences that need to be accounted for.…”
Section: Sex-dependent Effects Of Developmental Events: the Case Of Ementioning
confidence: 81%
“…Endocrine disruptors, including Bisphenol A and polychlorinated biphenyls , but also dietary phytoestrogens are known to affect neurodevelopment in rodents [163,165] Luteolin and quercetin have been reported to reduce autism symptoms in a small clinical trial [166].…”
Section: Persistent Organic Pollutants (Pop) and Polycyclic Aromatic mentioning
confidence: 99%
“…BPA has been reported to interfere with the metabolism and signaling of endogenous steroid hormones, particularly estrogen, and numerous studies, including our own, have repeatedly shown in multiple species that developmental exposure to BPA can perturb sexually dimorphic brain development and behavior, even at exposures below the current FDA NOAEL (representative examples include (Braun et al, 2011; Jasarevic et al, 2013; Kinch et al, 2015; Patisaul et al, 2012b; Rebuli and Patisaul, 2015; Sullivan et al, 2014; Wolstenholme et al, 2011)). Although this compounding evidence is compelling, because few published studies are evaluated to be of high utility for human risk assessment, there remains a lack of consensus on the potential risks BPA pose to the developing brain in humans.…”
Section: Introductionmentioning
confidence: 99%